2017
DOI: 10.1063/1.5004309
|View full text |Cite
|
Sign up to set email alerts
|

Thermal stability and Judd-Ofelt analysis of optical properties of Sm3+-doped sodium tellurite glasses

Abstract: Estimation of mean glandular dose for patients who undergo mammography and studying the factors affecting it AIP Conference Proceedings 1888, 020020 (2017) Abstract. Series of glasses based on (70-x) TeO2 -20Na2O -xSm2O3 (x=0, 0.3, 0.6, 1, 1.2, 1.5 mol%) have been prepared using melt-quenching technique. The nature of the glass has been confirmed using X-ray diffraction; it is found that the glass samples are amorphous in nature. The thermal stability of the glass has been determined by means of Differential T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The SEM micrographs of the glass samples, which Display in Figure 4, demonstrates the asymmetrical grain and various rod-type structures. SEM micrographs for all the glass samples have shown a homogeneous glassy phase (Mawlud et al, 2017b). Both dimensions show an irregular shape of grains and this structure can be observed for other glass samples.…”
Section: Edx Spectra and Sem Micrographmentioning
confidence: 53%
“…The SEM micrographs of the glass samples, which Display in Figure 4, demonstrates the asymmetrical grain and various rod-type structures. SEM micrographs for all the glass samples have shown a homogeneous glassy phase (Mawlud et al, 2017b). Both dimensions show an irregular shape of grains and this structure can be observed for other glass samples.…”
Section: Edx Spectra and Sem Micrographmentioning
confidence: 53%
“…On the other hand, the differences in Ω 4 and Ω 6 are interrelated to the long-range effect of the glass host. In 2017, Mawlud and other co-authors [58] reported that Ω 2 is affected by the strength of the bond between the rare-earth ions and the ligand ions. There is a high possibility of the asymmetry and polarization of the local structure surrounding the rare earth ion causing this phenomenon.…”
Section: Judd-ofelt Analysismentioning
confidence: 99%